2008
DOI: 10.1109/tcst.2007.916329
|View full text |Cite
|
Sign up to set email alerts
|

Stable Cooperative Surveillance With Information Flow Constraints

Abstract: Abstract-We consider a cooperative surveillance problem for a group of autonomous air vehicles (AAVs) that periodically receives information on suspected locations of targets from a satellite and then must cooperate to decide which AAV should search for each target. This cooperation must be performed in spite of imperfect intervehicle communications (e.g., messages with random but bounded delays), less than full communication connectivity between vehicles, uncertainty in target locations, and imperfect vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Accordingly, an important research problem in distributed surveillance is to design environment-based cooperative control laws for all coordinated agents such that the given area can be monitored efficiently. Recent research on distributed surveillance has been reported in [268]- [275], where a number of physical limitations were identified and considered such as time delay and uncertainties [271], [274], collision avoidance between agents [272], and heterogeneously distributed agents [274]. The current research is conducted under the assumption that each agent has enough power such that any designed control law can be applied.…”
Section: Surveillancementioning
confidence: 99%
“…Accordingly, an important research problem in distributed surveillance is to design environment-based cooperative control laws for all coordinated agents such that the given area can be monitored efficiently. Recent research on distributed surveillance has been reported in [268]- [275], where a number of physical limitations were identified and considered such as time delay and uncertainties [271], [274], collision avoidance between agents [272], and heterogeneously distributed agents [274]. The current research is conducted under the assumption that each agent has enough power such that any designed control law can be applied.…”
Section: Surveillancementioning
confidence: 99%
“…According to [13], the probability that UAV m detects target j with one look in a grid where the target j exists is defined as a m j , and l m (q, t k ) is the number of looks on grid q performed by UAV m at t k time instant. Hence, the history detection numbers on grid q performed by UAV m can be recorded as:…”
Section: Multiple Uavs Cooperative Surveillance Problem Formulationmentioning
confidence: 99%
“…Considering the communication delay, UAV m receives the detection history number that UAV n has searched on grid q can be expressed as h m,n (q, t k − τ n,m ) at t k time instant, where τ n,m is the arbitrary and finite communication delay, and L m,n (q, t k − τ n,m ) is the received corresponding total number of looks on grid q of UAV n. Hence, detection history information of the group stored by UAV m at t k time instant can be recorded asĥ m (q, t k ) = {h m,n (q, t k − τ n,m ), n ∈ U}. According to one look detection probability and history detection information, the detection probability of target j in grid q can be estimated [13] as:…”
Section: Multiple Uavs Cooperative Surveillance Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last one decade or so, computer-aided simulation of natural swarms has attracted a lot of research interest. It has been perceived through the efforts of the researchers that the functional principles from such biological swarms can be utilized in engineering for the development and control of multi-agent systems, such as the formation control of multi-robot systems [2,3], unmanned land, sea, or air vehicles [4,5], surveillance [6], rendezvous [7], coverage control on mobile sensing networks [8], and so on. Recently the concept of Computing Networks [9] has been developed to generalize swarm and neural architectures.…”
Section: Introductionmentioning
confidence: 99%